PERLINDUNGAN KONSUMEN TERHADAP DEPOT AIR MINUM ISI ULANG YANG MENYEBABKAN HEPATITIS A PADA TAHUN 2018 DI KOTA SINGKAWANG - NIM. A1011201299, AMOR PANGESTU (Jurnal Fatwa Hukum, 2024)
Abstract  Law Number 08 of 1999 concerning Consumer Protection is the legal basis for solving problems in Indonesia.   In 2018 in Singkawang City, there was an outbreak of Hepatitis A disease at a suspected drinking water depot. The Hepatitis A Mitigation Team of the Ministry of Health and the West Kalimantan Provincial Government has reviewed the location of Singkawang in an effort to monitor and prevent the spread of hepatitis A disease in the local area, there were around 242 cases of Singkawang residents suspected of being infected with the hepatitis A virus in 2018. Hepatitis A patients spread in a number of sub-districts in the city of Singkawang. Of the 242 suspected cases, four of them tested positive for hepatitis A.This study uses a type of Empirical legal research with the approach in this study is with a qualitative approach. This means that the data taken is not from numbers, but from interviews, field notes, personal documents, and other official documentsThe results of the legal analysis show that the consumer protection of refillable drinking water depots in 2018 in Singkawang City is not fully in accordance with Government Regulation Number 58 of 2001 concerning Supervision of the Implementation of Consumer Protection which made in 2018 the emergence of Extraordinary Cases of Hepatitis A. The Singkawang City Government, the Ministry of Health and the Singkawang City Health Office, made various efforts to resolve the case,   namely by calling refillable drinking water depot business actors to be given directions in accordance with Government and Ministry of Health regulations to reduce hepatitis A cases in Singkawang City.Keywords: Consumer Protection, Drinking Water Depot      Abstrak  Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen menjadi dasar hukum dalam penyelesaian masalah di Indonesia. Pada 2018, wabah Hepatitis A terjadi di Kota Singkawang, diduga terkait depot air minum isi ulang. Tim Mitigasi Hepatitis A dari Kementerian Kesehatan dan Pemerintah Provinsi Kalimantan Barat memantau penyebaran penyakit ini. Terdapat 242 kasus dugaan infeksi, dengan empat kasus terkonfirmasi positif. Kasus tersebar di sejumlah kecamatan di Singkawang.Penelitian ini menggunakan metode hukum empiris dengan pendekatan kualitatif, mengandalkan data dari wawancara, catatan lapangan, dokumen pribadi, dan dokumen resmi lainnya. Analisis hukum menunjukkan bahwa perlindungan konsumen depot air minum isi ulang di Singkawang pada 2018 belum sepenuhnya sesuai dengan Peraturan Pemerintah Nomor 58 Tahun 2001 tentang Pengawasan Perlindungan Konsumen. Hal ini memicu munculnya wabah Hepatitis A.Upaya penyelesaian dilakukan oleh Pemerintah Kota Singkawang bersama Kementerian dan Dinas Kesehatan, termasuk memanggil pelaku usaha depot air minum untuk diberikan arahan sesuai peraturan guna menekan kasus Hepatitis A.Kata kunci : Perlindungan Konsumen, Depot Air Minum